A conjectura lógica de Jacques Lacan: a lógica como ciência do real - Mardem Leandro Silva (2019)
This thesis proposes as an investigation about Lacan's relation with logic. To do so, it is based on the logical reading that Lacan undertakes on the Freudian hypothesis of the existence of the unconscious, in which the concept of representation is taken for its significant reason and in which the Lacanian proposal derives the unconscious from what he calls of pure logical, namely the signifier. But if the unconscious stems from pure logic, then what are the conditions of possibility for this logic? Is this logic of the unconscious on the same logical platform as the other logics that Lacan made extensive use of to think analytic experience, or is it still - in Miller's perspective on the logic of the signifier - a logic of the origin of logic? These questions derive from the fact that the unconscious is formulated from another logical perspective, unaware of the principles of classical logic, but in close relation to its impasses and paradoxes. Lacan, throughout his work, knew how to draw consequences from these impasses to highlight in logic their impossible and thus propose their organon: the logic of the signifier and this to logic as the science of the real. From the various logical models proposed by Lacan, it is hypothesized that they are a set of hypotheses that are organized from the perspective of a logical conjecture. To support and justify this hypothesis, we start from the analysis of Freud's work, resuming the Lacanian gesture of deriving its concept of signifier from the Freudian concept of representative of representation. The Freudian notion of the language apparatus present in the monograph is described. The interpretation of aphasias, from 1891, as the foundation of the psychic apparatus of 1900. The Freudian proposition of the unconscious hypothesis implies, implicitly or explicitly, a logical correspondent for think about its mechanisms of operation. From the logic of the unconscious functioning proposed by Freud to Aristotle to the science of mathematical logic, Lacan's logical influences are innumerable. Despite Lacan's extensive, multiple, and paradoxical use of logic, his interest is nonetheless rooted in the logical impossibility evacuated from the scope of logistic logic. In this sense, Lacan would be a logician who would defy and subvert logic. This thesis aims to investigate the consequences of Lacan's relationship with the logical field in the context of the formulation of what is called to be his logical conjecture, a conjecture that purports not to be demonstrable, as psychoanalysis questions the very foundation of reason. apoditic. Thus, we seek to highlight that the Lacanian conjecture makes the limits of the writing of science transparent, to the point where they are closely articulated with the limits of writing of logic. In view of this, it is endorsed the thesis that Lacan promotes a subversion of logic by writing, via mathema, the limits of the writing of logic itself, thus presenting a certain inductive reading of the letter. Without thereby incurring trivial logic or converting psychoanalysis into a sterile logicist practice or trying to reduce everything to pure logic, since not everything is significant.